Sugarcane Biomass as a Source of Biofuel for Internal Combustion Engines (Ethanol and Acetone-Butanol-Ethanol): A Review of Economic Challenges - Algayyim S.J.M.; Yusaf T.; Hamza N.H.; Wandel A.P.; Fattah I.M.R.; Laimon M.; Rahman S.M.A. (MDPI, 2023)
Acetone; Bacteria; Bagasse; Biofuels; Blending; Ethanol; Internal combustion engines; Waste incineration; Acetone butanol ethanols; Acetone-butanol-ethanol blend; Chemical pre-treatment; Commercial process; Economic challenges; Ethanol blend; Liquid biofuels; Pretreatment technology; Sugar-cane bagasse; Sugarcane; Fermentation